2008
DOI: 10.1143/jjap.47.7574
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Temperature Dependences of Ferroelectric and Magnetic Properties in Polycrystalline Co-Substituted BiFeO3 Films

Abstract: Multiferroic Co-substituted BiFeO3 films were fabricated by chemical solution deposition method followed by post deposition annealing at various temperatures. The substitution of cobalt of B-sites for iron in BiFeO3 was promoted at relatively high temperatures. The B-site substitution by cobalt promoted increases in saturation magnetization and spontaneous magnetization. By substitution, leakage current density was suppressed in a high-electric-field region, and ferroelectric hysteresis (P–E) loops became meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
(13 reference statements)
1
18
0
Order By: Relevance
“…Chemical substitutions have also been widely explored to induce a net magnetization in BiFeO 3 . Although there have been many reports on enhanced magnetization by chemical modification, surprisingly, the origin of the magnetic signal is unclear in nearly all cases . This is because macroscopic magnetic measurements cannot distinguish the intrinsic magnetic signal of BiFeO 3 from that of magnetic impurities such as γ‐Fe 2 O 3 .…”
Section: Chemical Substitution Of Bifeo3mentioning
confidence: 99%
“…Chemical substitutions have also been widely explored to induce a net magnetization in BiFeO 3 . Although there have been many reports on enhanced magnetization by chemical modification, surprisingly, the origin of the magnetic signal is unclear in nearly all cases . This is because macroscopic magnetic measurements cannot distinguish the intrinsic magnetic signal of BiFeO 3 from that of magnetic impurities such as γ‐Fe 2 O 3 .…”
Section: Chemical Substitution Of Bifeo3mentioning
confidence: 99%
“…Because Bi 3+ and Ca 2+ have similar radii, which is the same as Fe 3+ , Cu 2+ and Ti 4+ . Hence, it is deduced that Ca 2+ occupies site A, Cu 2+ and Ti 4+ occupy site B in the solution to form a more stable perovskite structure.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports on the doping of transition metal ions such as Co, Cr, Ti, Mn, Zn etc. at B-site (Fe-site) in BFO with the enhance magnetoelectric properties [16,17] . It is observed that the electrical properties of BFO ceramics improved by doping of trivalent La 3 + and other dopants at Bi 3 + site.…”
Section: Introductionmentioning
confidence: 99%